The Effect of Landscape in Sustainability of Schools - Sana’ Sati’ Abbas; Aseel Jafer Jasem (Iraqi Journal of Architecture and Planning)
The landscape in sustainable schools acquires great importance in the knowledge era, which is of essential development. This era deals with the components of educational system, concentrates on the educator, transfers teacher from the impart teacher to a trainer teacher, and ensure on selfeducation activity to achieve the aim of modern education, which visualize by sustainable teaching or teaching to the sake of sustainable development. Therefore, it is necessary to adopt the Environment school with the new educational needs, which ask to the development of the relationship between teachers and students and the openness on outdoor environment. So the aim of this paper is to highlight the role of schools landscape and its importance in the reaction of students with their setting, through special characteristics. Literature review shows the importance of landscape in sustainable schools, in achieving sustainability in (education, environmental, economic, social, easthic, psychology, security sides).The research problem was that (the absence of the importance of the landscape school in the students education locally according to the modern educational requirement), while the research hypothesis was that (education and interaction of student with landscape correlated with the rehabilitation of this landscape). To solve this problem the paper will study (the sustainable school and sustainable landscape). To test the research hypothesis the research built a questioner, and choose two types of samples, the first one are models of primary schools in Baghdad/ second Rusafa sector , while the second one is the sixth year primary school students. The research findings that there is a well , from the student to have outdoor lessons, but this well is listless and face many obstacles, the most important one is absence of a qualify landscape, the second one is the nature of the curriculum, which is taken in side classes, and which is mostly by impute method, which made the students concentrate on the theoretical side more than practical one; this lead them to spent more times inside classes. So the landscape was used for playing only. The research submit design model for landscape in one of the primary school, which is considered as rehabilitation to this landscape toward a sustainable landscape.